Secondary Chondrosarcoma Presenting with Symptoms Similar to Thoracic Outlet Syndrome - Hiroshi Kobayashi; Masachika Ikegami; Tetsuo Ushiku; Masaki Anraku; Takahiro Ohki; Yusuke Shinoda; Sakae Tanaka; Hirotaka Kawano (Case Reports in Orthopedics)
Thoracic outlet syndrome (TOS) is caused by heterogeneous factors that compress the brachial plexus and subclavian artery; tumor is rarely a cause of TOS. Here, we present the case of a 26-year-old man with secondary chondrosarcoma arising from osteochondroma of the left clavicle causing TOS, with a direct compression of the brachial plexus and subclavian artery. Immediately after surgery, the symptoms of TOS reduced. To our knowledge, this is the first case of a secondary chondrosarcoma of the clavicle causing TOS, which is possibly the key symptom for diagnosing malignant transformation of osteochondroma of the clavicle.